2015
DOI: 10.1111/vop.12267
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant rodenticide toxicity in six dogs presenting for ocular disease

Abstract: Anticoagulant rodenticide toxicity can present with predominantly ocular manifestations. Rodenticide ingestion should be considered in dogs with unilateral or bilateral subconjunctival hemorrhage, exophthalmos, and orbital pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 12 publications
2
23
0
1
Order By: Relevance
“…Similar findings are reported for human non-accidental injuries and it has been suggested that subconjunctival haemorrhage may be a sentinel injury for physical abuse in children (Kleemann et al 1995, Spitzer et al 2005, Betts et al 2017. However, there is also evidence in the veterinary and human literature that subconjunctival haemorrhage is not specific for abuse but also occurs in accidental or self-inflicted injuries (Sperry 1993, Alexander & Jentzen 2011, Bamber et al 2014, Ghazanfari-Nasrabad et al 2016, Intarapanich et al 2016) and also associated with systemic diseases including coagulopathies (Griggs et al 2016), envenomation (Martins et al 2016) and vasculitis (Davidson et al 1989). To avoid overestimating the likelihood of abuse, it is important that veterinarians are aware of the range of possible underlying causes for subconjunctival haemorrhage in dogs.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Similar findings are reported for human non-accidental injuries and it has been suggested that subconjunctival haemorrhage may be a sentinel injury for physical abuse in children (Kleemann et al 1995, Spitzer et al 2005, Betts et al 2017. However, there is also evidence in the veterinary and human literature that subconjunctival haemorrhage is not specific for abuse but also occurs in accidental or self-inflicted injuries (Sperry 1993, Alexander & Jentzen 2011, Bamber et al 2014, Ghazanfari-Nasrabad et al 2016, Intarapanich et al 2016) and also associated with systemic diseases including coagulopathies (Griggs et al 2016), envenomation (Martins et al 2016) and vasculitis (Davidson et al 1989). To avoid overestimating the likelihood of abuse, it is important that veterinarians are aware of the range of possible underlying causes for subconjunctival haemorrhage in dogs.…”
Section: Introductionsupporting
confidence: 66%
“…) and also associated with systemic diseases including coagulopathies (Griggs et al . ), envenomation (Martins et al . ) and vasculitis (Davidson et al .…”
Section: Introductionmentioning
confidence: 99%
“…No information on the possible causes were given. Griggs et al (2016) described orbital and ocular disease in 6 dogs diagnosed with anticoagulant rodenticide toxicity. One of these patients showed a severe and acute unilateral orbital haemorrhage and remained blind.…”
Section: Introductionmentioning
confidence: 99%
“…25 However, these poisons are nonspecific and may kill nontarget animals, such as companion animals, that consume them. 5 They can also disable or kill predators that eat rats killed by poisons, such as hawks and owls. 17 The worst possible scenario is the accidental poisoning of humans, which can lead to death.…”
Section: Introductionmentioning
confidence: 99%